Evaluation of the growth and quality of lettuce (iLactuca sativa/i L.) in a closed recirculating hydroponic system (2017)
The production of lettuce in hydroponic systems with a recirculating nutrient solution has been growing, so it is necessary to evaluate the growth and quality of production under this system. Two harvest cycles were evaluated, comparing the behavior of physiological variables and growth rates on lettuce plants in a hydroponic system with a plastic cover. Lettuce plants were planted at 30 days after germination in an NFT hydroponic system. Nutrient solutions were prepared with sources of potassium nitrate, calcium nitrate, urea phosphate, magnesium sulfate and a source of minor nutrifeed. The second cycle had the highest total dry mass and leaf area index (LAI) at 43 days after transplant (dat). The relative growth rate (RGR) declined over time. The absolute growth rate (AGR) resented a sigmoid behavior as a gaussian bell shape; the leaf area index (LAI) increased until 43 dat, with the second cycle presenting the highest value; the net assimilation rate (NAR) decreased over time, with the second cycle having the highest value at 22 dat. The chlorophyll content for this variety was low, with a yellow pigmentation in the plant. The stomatal conductance (SC) in the two cycles at transplant time presented low values caused by the stress leaded by an imbalance in the pH of the solution, when the plants adapted to the system, this value increased.